2021
DOI: 10.3390/rs13152978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Correction of Elevation Angle Influence for Coastal GNSS-R Ocean Altimetry

Abstract: The elevation angle influence on coastal GNSS-R ocean code-based altimetry for GPS signals (L1 C/A and L5) and BDS B1 signals is investigated, and the corresponding correction method is presented. The study first focuses on the coastal ocean altimetry method, including the general experiment geometry and the code delay estimation using the single-point tracking algorithm. The peak power and the maximum first derivative are used as the location of the specular point. Then, the sensitivity of the height retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…One is the peak point of the waveform; the other is the peak point of the derivative waveform [35]. In [36], it was found that the peak of the waveform can provide better performance than the peak of derivative waveform. Therefore, we used the peak of the waveform as the arrival of the reflected signal.…”
Section: A Ground-based Gnss-r Code-level Altimetrymentioning
confidence: 99%
“…One is the peak point of the waveform; the other is the peak point of the derivative waveform [35]. In [36], it was found that the peak of the waveform can provide better performance than the peak of derivative waveform. Therefore, we used the peak of the waveform as the arrival of the reflected signal.…”
Section: A Ground-based Gnss-r Code-level Altimetrymentioning
confidence: 99%
“…The sea surface height (SSH) is a key parameter in marine research and contributes signi cantly to the development of high-precision ocean gravity elds and the detection of changes in the dynamic environment of the ocean (Li et al 2020;Li et al 2014; Zhang et al 2021). SSH can be categorized into nearshore and oceanic types, each requiring different monitoring strategies due to their distinct geographic characteristics (Antony et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers utilize Global Navigation Satellite System (GNSS) re ection signals to observe SSH changes due to continuous GNSS development. Numerous studies exist (Song et al 2020; Zhang et al 2021;Zhu et al 2023). In 2000, Anderson used traditional geodetic GNSS receivers to establish an interferometric model from signal-to-noise ratio (SNR) observations.…”
Section: Introductionmentioning
confidence: 99%
“…The leading edge derivatives (LEDs) of spaceborne GNSS-R waveforms are employed and enhanced to retrieve sea surface height in [36]. A correction method is introduced for satellite altitude angles in the detection of sea surface height in [37]. The authors employ model-driven and data-driven methodologies in this study to improve the effects of elevation angle.…”
Section: Introductionmentioning
confidence: 99%